A perspective on the mechanisms of herbal medicine for cognitive impairment - Si-yuan Zheng; Si-yuan Zheng; Xiao-qing Zhou (Frontiers in Neurology)
Cognitive impairment (CI) represents a critical public health burden exacerbated by aging populations and inadequate therapeutic options. Conventional treatments usually target single molecules, which limits their effectiveness in addressing the complex pathology of CI. In contrast, herbal medicine provides a systems-level therapeutic approach by simultaneously regulating multiple signaling pathways. This narrative perspective summarizes recent evidence on the pharmacological mechanisms through which herbal therapies mitigate CI. A focused literature review was performed to identify preclinical and clinical studies that emphasize the regulation of key pathways, including PI3K/Akt, Nrf2/HO-1, NF-κB, and BDNF/TrkB. These pathways act synergistically to reduce oxidative damage, inhibit pro-inflammatory cytokine production, and promote neuroplasticity. Representative compounds such as ginsenosides, catalpol, and standardized extracts from Ginkgo biloba and Huperzia serrata exhibit promising effects on these molecular pathways. Compared with monotherapies, herbal medicines offer a broader pharmacodynamic spectrum and potentially fewer adverse effects. These findings support the integration of herbal medicine into treatment strategies for CI and emphasize the need for high-quality clinical trials and mechanistic studies to validate and optimize its application.